2018
DOI: 10.4103/sjg.sjg_261_18
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation versus surgical resection in elderly patients with early-stage hepatocellular carcinoma in the era of organ shortage

Abstract: Background/Aims:To compare the survival benefits of surgical resection (SR) with those of radiofrequency ablation (RFA) in elderly patients (≥65 years) with single hepatocellular carcinoma (HCC) ≤5 cm.Patients and Methods:Using the Surveillance, Epidemiology, and End Results database, a total of 461 patients who underwent SR and 575 patients who underwent RFA were enrolled from 2004 to 2012. Overall survival (OS) and liver-cancer-specific survival (LCSS) comparisons were conducted between the two groups before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…However, there are also some drawbacks that need to be noticed. In fact, there is a lot of information that is unavailable in SEER but is closely correlated with post-operative survival, such as the details of the surgery, laboratory results, postoperational radiation, and systemic chemotherapy, as well as the performance status and severity of dysfunction of the liver or other organs (7,16,20,24). Although the fibrosis score is provided, it is not sufficient to estimate the severity of cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are also some drawbacks that need to be noticed. In fact, there is a lot of information that is unavailable in SEER but is closely correlated with post-operative survival, such as the details of the surgery, laboratory results, postoperational radiation, and systemic chemotherapy, as well as the performance status and severity of dysfunction of the liver or other organs (7,16,20,24). Although the fibrosis score is provided, it is not sufficient to estimate the severity of cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is also undetermined whether these elderly patients benefit substantially more from the more radical surgical therapies, e.g., hemihepatectomy or liver transplantation, compared with the less invasive surgeries, such as radio-frequency ablation or segmental liver resection. For the present, there are few studies that investigate this issue with convincing and dependable hugescale data such as ours (6,7).…”
Section: Introductionmentioning
confidence: 97%
“…In the comparison of RFA and surgical resection by postoperative outcomes, contradictory results were yielded. Peng et al[73] reported that patients having RFA had better outcomes than those having surgical resection, while Bauschke et al[74] and Yu et al[75] reported better outcomes for surgical resection. Another retrospective study by Jiang et al[76] concluded that RFA should be recommended for elderly patients (age > 65 years) with HCCs ≤ 20 mm while surgical resection would be a better treatment for HCCs of 21-50 mm in elderly patients.…”
Section: Radiofrequency Ablationmentioning
confidence: 99%
“…Anastomotic leakage following gastrectomy for gastric cancer is a life-threatening complication, and revisional surgery has a high mortality rate. The treatment includes conservative management, endoscopic treatment, and surgery[ 5 ]. Surgery is generally recommended for patients in critical condition.…”
Section: Discussionmentioning
confidence: 99%